Yield Evaluation of Several Tomato Strains from the Cross-Breeding Product of Mawar x Chung - BDR, Muh. Farid; Anshori, Muhammad Fuad; Mantja, Katriani; Ridwan, Ifayanti; Mustafa, Marlina; Adnan, Adnan (Agrotech Journal, 2023)
The unavailability of high-yielding varieties can cause low production of tomatoes. Excellent variety construction in plant-breeding programs is possible as an effort to solve the tomato cultivation problem. This study aimed to evaluate the yield of several tomato strains from the cross-breeding product of Mawar Ã— Chung. This study was conducted at the experimental garden, Faculty of Agriculture, Hassanuddin University from April to July 2023. From the results, a strain with high productivity level was obtained from the KM 10.10.6 (g6), which produced an average of 1432.64 g and was significantly different from both parent plants. This strain also had high heritability levels of plant height, dichotomic height, number of branches, flowering period, harvesting period, number of fruit bunches, number of fruits, fruit length, fruit diameter, fruit weight and productivity. Moreover, this strain had four characteristics that positively correlated to production, namely plant height, stem diameter, number of branches, and number of fruits